The biological effects of long-term exposure of human bronchial epithelial cells to total particulate matter from a candidate modified-risk tobacco product. (August 2018) - van der Toorn, Marco; Sewer, Alain; Marescotti, Diego; Johne, Stephanie; Baumer, Karin; Bornand, David; Dulize, Remi; Merg, Celine; Corciulo, Maica; Scotti, Elena; Pak, Claudius; Leroy, Patrice; et al.
Abstract: Cigarette smoking is the leading cause of preventable lung cancer (LC). Reduction of harmful constituents by heating rather than combusting tobacco may have the potential to reduce the risk of LC. We evaluated functional and molecular changes in human bronchial epithelial BEAS-2B cells following a 12-week exposure to total particulate matter (TPM) from the aerosol of a candidate modified-risk tobacco product (cMRTP) in comparison with those following exposure to TPM from the 3R4F reference cigarette. Endpoints linked to lung carcinogenesis were assessed. Four-week 3R4F TPM exposure resulted in crisis and epithelial to mesenchymal transition (EMT) accompanied by decreased barrier function and disrupted cell-to-cell contacts. By week eight, cells regained E-cadherin expression, suggesting that EMT was reversible. Increased levels of inflammatory mediators were noted in cells treated to 3R4F TPM but not in cells treated to the same or a five-fold higher concentration of cMRTP TPM. A 20-fold higher concentration of cMRTP TPM increased oxidative stress and DNA damage and caused reversible EMT. Anchorage-independent growth was observed in cells treated to 3R4F or a high concentration of cMRTP TPM. 3R4F TPM-derived clones were invasive, while cMRTP TPM-derived clones were not. Long-term exposure to TPM from the cMRTP had a lower biological impact on BEAS-2B cells compared with that of exposure to TPM from 3R4F. Highlights: A cellular model featuring chronic exposure may be a suitable in vitro approach for cancer risk assessment. Short-term exposure to tobacco product TPM resulted in cellular crisis and EMT. Long-term exposure to tobacco product TPM resulted in cellular transformation. TPM from THS2.2 had a lower biological impact then TPM from 3R4F. Heating rather than combusting tobacco may reduce the risk of lung cancer.